THEMATIC ANALYSIS OF JUAN SOLANA’S UPSIDE DOWN MOVIE - Valdy Rifzki and Indra Hartoyo (LINGUISTICA, 2017)
The objectives of the study are to investigate and explain about love languages found and used in the Upside Down movie. The data were analyzed by finding the words or statements of main character in the movie script. Chapman’s theory of love languages was applied. Based on its form, Chapman divides love languages into 5 kinds, they are (1) words of affirmation, (2) quality time, (3) receiving gifts, (4) acts of service, and (5) physical touch. The method used in this research was descriptive qualitative. The data were analyzed by finding the words or statements by use main character in the movie script. The result shows that, there are four kinds of love languages used. The findings show not all kinds of Love Languages used in the movie. According to the meaning of each kind, Acts of Service wasn’t used in the movie because the theme of the movie is about love struggle, and love languages has an important role because the using of it is to build up the relationship.